ANALISIS DAMPAK BIMBINGAN TEKNIS HUKUM ACARA PENGUJIAN UNDANG-UNDANG DI MK RI TERHADAP ADVOKAT PERADI - Karlina, Yunawati; Putra, Irwan Sapta (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
The article discusses the impact analysis of the PUU Procedural Law Guidance held by the Constitutional Court on Peradi Advocates throughout Indonesia. The purpose of the study, first is to find out how the impact of the PUU Procedural Law Guidance held by the Constitutional Court on the understanding of Peradi Advocates? Second, to find out the benefits for peradi advocates who follow Bimtek? This research method is normative law, with a statutory approach, a historical approach and a case approach. Primary, secondary and tertiary data sources. Data collection techniques by means of literature study, qualitative juridical data analysis. The results of the first study can increase the understanding and knowledge of lawyers peradi about the authority of the Constitutional Court. Secondly, they can construct a good and correct PUU application, can comprehensively control the PUU application material, get a conference overview of the PUU application flow starting from registration, document preparation and preliminary trial to the verdict trial. Suggestions for the future of the technical guidance are still carried out considering the magnitude of the impact and benefits of the technical guidance for advocates throughout Indonesia.